2017
DOI: 10.1007/s40471-017-0115-y
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities in Studying the Epidemiology of Ovarian Cancer Subtypes

Abstract: Purpose of review Only recently has it become clear that epithelial ovarian cancer (EOC) is comprised of such distinct histotypes--with different cells of origin, morphology, molecular features, epidemiologic factors, clinical features, and survival patterns—that they can be thought of as different diseases sharing an anatomical location. Herein, we review opportunities and challenges in studying EOC heterogeneity, Recent findings The 2014 World Health Organization diagnostic guidelines incorporate accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 107 publications
1
47
0
1
Order By: Relevance
“…The majority of studies showed the enhanced expression of class I HDACs in solid human tumours and in locally advanced, dedifferentiated, strongly proliferating tumours. There is a growing body of evidence that the expression of class I HDACs is increased in ovarian carcinomas (4), and this is suspected not only of playing a significant role in carcinogenesis, but also of contributing towards resistance to chemotherapeutic agents used for treating ovarian cancer (23). This is in agreement with our observation that the highest expression was observed in OVCAR-3 cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The majority of studies showed the enhanced expression of class I HDACs in solid human tumours and in locally advanced, dedifferentiated, strongly proliferating tumours. There is a growing body of evidence that the expression of class I HDACs is increased in ovarian carcinomas (4), and this is suspected not only of playing a significant role in carcinogenesis, but also of contributing towards resistance to chemotherapeutic agents used for treating ovarian cancer (23). This is in agreement with our observation that the highest expression was observed in OVCAR-3 cells.…”
Section: Discussionsupporting
confidence: 92%
“…A common finding in cancer cells is the overexpression of HDACs and their increased activity, leading to the altered expression and activity of numerous proteins involved in carcinogenesis. Although the knowledge of ovarian cancer is growing, there is still no proper therapy for the prevention and treatment of this type of cancer (4). There is a growing body of evidence showing that the expression of class I HDACs is increased in ovarian carcinomas (5)(6)(7) and this is suspected not only of playing a significant role in carcinogenesis, but also of contributing toward resistance to chemotherapeutic agents used for treating ovarian cancer.…”
mentioning
confidence: 99%
“…EOC represents the seventh most commonly diagnosed cancer among women globally and has a 46% 5year survival rate after diagnosis. One of the main factors contributing to the high death-to-incidence ratio is the advanced stage of disease at the time of diagnosis [2]. The cause of this disease is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancer (OC) is one of the most common cancers with a high mortality rate, causing approximately 140 000 deaths each year in the United States 1 . It represents the seventh most commonly diagnosed cancer among women worldwide with an estimated 5‐year survival of 40%–45% 2,3 . The poor survival outcomes of women with OC are related to extensive peritoneal spread at the time of diagnosis.…”
Section: Introductionmentioning
confidence: 99%